Incidental EBV-positivity in paediatric post-transplant specimens demonstrates the need for stringent criteria for diagnosing post-transplant lymphoproliferative disorders. Issue 3 (15th November 2016) - King, Rebecca L; Paessler, Michele E; Howard, Matthew T; Wertheim, Gerald B
Abstract : Aims: To examine the need for minimal diagnostic criteria for post-transplant lymphoproliferative disorders (PTLD) in children, we sought to determine the rate of incidental Epstein-Barr virus (EBV)-positivity in tissues from organ transplant recipients (OTR). Methods: EBV in situ hybridisation (ISH) was done retrospectively on tissue from 34 paediatric autopsies of OTR and paediatric tonsillectomy specimens from non-OTR (96) and OTR (6). Patients with a history of PTLD were excluded from both data sets. Results: EBV-positivity was found incidentally in 2/34 autopsy cases (5.9%). Median time from transplant to death for all patients was 12.8 months (range 0.1–153 months). Median time between transplant and death in EBV-positive cases was 34 months. EBV was positive in 26/102 tonsils (25%). Among tonsils from OTR, 4/6 (67%) were EBV-positive. Conclusions: These findings reinforce the need for strict morphological and clinical criteria, other than EBV-positivity, when diagnosing PTLD in the paediatric population.